Social support to improve the self-care ability of people with mental disabilities: a qualitative study in the “Kampung Tunagrahita” - Dahlia Novarianing Asri; Dian Ratnaningtyas Afifah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2020)
The objectives of this research are to describe and explain types of social support provided by families and residents of surrounding communities to individuals with mental disabilities in the “kampung tunagrahita” of mentally disabled people in Ponorogo Regency. This research used a qualitative descriptive approach along with its case study design. The data collection was undertaken through in-depth interviews, documentation, and passive observation. The sources of data were derived from main informants, events or activities that provided the social support to improve the ability of people with mental disabilities, and documents in the form of background data on the people with mental disabilities and other pertinent documents. The research subjects were dietermined using a purposive sampling technique, and the data analysis used an interactive analysis model. The results show that families, normal citizens, and village government in Jambon district, Ponorogo Regency provide the social support to people with mental disabilities through the provision of self-care skills training, information and assistance in taking care of family members with mental disabilities. Likewise, the much-needed skills training is set to produce works worth considering.